Kegiatan Pengabdian Masyarakat Mengenai Penapisan Penyakit Kardiovaskular dengan Pemeriksaan Kadar Kolesterol dan HDL Sejak Dini pada Masyarakat Kelurahan Grogol - Yudhitiara, Novia; Santoso, Alexander Halim; Gunaidi, Farell Christian; Riadi, Seravin Janet; Kasvana, Kasvana (PPNI UNIMMAN, 2025)
Dyslipidemia is one of the most common metabolic disorders among the productive-age population and plays a major role in increasing the risk of cardiovascular diseases, including coronary heart disease and stroke. This condition often remains asymptomatic in its early stages, making regular monitoring of cholesterol and HDL levels a critical step in the early detection of atherosclerosis risk. Community-based screening programs revealed that 42.25% of participants had elevated total cholesterol levels, while 26.76% had very low HDL levels and 43.66% had low HDL levels. These findings highlight the urgency of early detection of dyslipidemia to prevent long-term complications that may impair individual quality of life. Through timely interventions involving nutritional education, dietary modifications, and increased physical activity, blood lipid levels can be effectively managed to prevent the progression of cardiometabolic disease and support long-term heart health.